2012
DOI: 10.1016/j.cub.2012.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size Control in Yeast

Abstract: Cell size is an important adaptive trait that influences nearly all aspects of cellular physiology. Despite extensive characterization of the cell cycle regulatory network, the molecular mechanismscoupling growth to division, and thereby controlling cell size, have remained elusive. Recent workin yeast has reinvigorated the size control field and suggested provocative mechanisms forthe distinct functions of setting and sensing cell size. Further examination of size sensing models based on spatial gradients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
347
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(371 citation statements)
references
References 157 publications
(164 reference statements)
23
347
0
1
Order By: Relevance
“…Cells have to reach a certain critical size at which cell-cycle transitions are triggered, such as G1-S or G2-mitosis (Ivanov, 1971;Dobrochaev and Ivanov, 2001;Dolznig et al, 2004;Yang et al, 2006;Turner et al, 2012;Robert et al, 2014). Therefore, along the PD it is expected that cells are equal to or smaller than the critical size of dividing cells (L critD ).…”
Section: Determination Of the Pd/td Boundary By The Msc Approach Coinmentioning
confidence: 99%
“…Cells have to reach a certain critical size at which cell-cycle transitions are triggered, such as G1-S or G2-mitosis (Ivanov, 1971;Dobrochaev and Ivanov, 2001;Dolznig et al, 2004;Yang et al, 2006;Turner et al, 2012;Robert et al, 2014). Therefore, along the PD it is expected that cells are equal to or smaller than the critical size of dividing cells (L critD ).…”
Section: Determination Of the Pd/td Boundary By The Msc Approach Coinmentioning
confidence: 99%
“…In the budding yeast Saccharomyces cerevisiae, cell division is known to be coordinated with cell growth [1][2][3][4][5][6] (reviewed in [7]). This dependence between growth and division is most noticeable in daughter cells that, owing to the asymmetric manner of budding yeast division, are born smaller than their mothers (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hysteresis behavior in cell cycle kinetics in response to changes in pheromone concentration is reproduced theoretically using our model [12]. We deduce that Cln3 is the primary driver of reentry and that the accumulation of Far1 directly reinforces arrest.Finally, we confirm that Far1 accumulates slowly to ensure stability against size-dependent increases in Cln3 activity [21], because the small fluctuation of Cln3 level can be filtered due to the increase of CDK-threshold. Whereas fast phosphorylation cycles of Far1 allow rapid responses including rapid activation and reentry.…”
mentioning
confidence: 62%
“…However, if a cell enters S phase later, it will waste resources. Therefore, the decision about the G1/S transition point is critical.Experimental studies have demonstrated that the G1/S transition point is connected to the cell volume [19][20][21]. A recent study demonstrated that the switch-like G1/S transition is driven by the degradation of Sic1 and that the timing of Sic1 destruction is set by Cln1/2-Cdc28 [10].…”
mentioning
confidence: 99%